مكونات الغلة ودليل الحصاد للقمح القاسي Triticum durum تحت ظروف الساحل السوري - قبيلي, صالح; خوري, بولص (Latakia University Journal -Biological Sciences Series, 2018)
تم تقدير درجة التوريث، التقدم الوراثي والارتباط في عشائر القمح القاسي (Triticum durum) الناتجة من تهجينات بين الأصناف. أظهرت عشائر الجيل الثاني للهجين أفياشيك X 65 ليكورم 78/368 انعزالاً فائق الحدود لصفة عدد الحبوب في السنبلة إضافة للغلة الحبية ودليل الحصاد. وبينت درجة التوريث العالية المصحوبة بتقدم وراثي ملحوظ في هذا الهجين أهمية تأثير التباين الوراثي التراكمي لهذه الصفات، وتميزت غالبية الصفات عموماً بعلاقات ارتباطية موجبة مع الغلة الحبية لدى الآباء وعشائر الجيل الثاني. وبالتالي، لزيادة الغلة الحبية، يجب أن يتركز الانتخاب في عشائر الجيل الثاني لصفة عدد الحبوب الأعلى، والإشطاءات السابلة، ودليل الحصاد المرتفع. A study was conducted to estimate heritability, genetic advance and correlation in durum wheat (tritium durum) populations derived from on intercultivar cross. The F2 Populations showed cross aphiachik 65 X Licorm 78/368 transgressive segregation for a number of grains per ear, grain yield, and harvest index. High heritability combined with considerable genetic advance in this cross indicated that additive gene variance effect was important for these traits. At the same time, all characters were generally correlated with grain yield in parents and the F2 population. Thus, to increase grain yield, selection in the F2 population shoud be having high grains number, the number of fertile tillers, and high harvest index, for plants.